Isla and the happily ever after - Perkins, Stephanie (New York, New York Dutton Books, 2014)
Isla has had a crush on classmate Josh since their freshman year at the School of America in Paris, but after a chance encounter over the summer in Manhattan they return to France for their senior year where they are forced to confront challenges every young couple in love must face
1
Keywords: JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Social Issues / Dating & Sex; JUVENILE FICTION / Social Issues / Friendship; Boarding schools -- Fiction; Foreign study -- Fiction; Love -- Fiction; Schools -- Fiction; France -- Fiction; Paris (France) -- Fiction